2022
DOI: 10.3390/app12020537
|View full text |Cite
|
Sign up to set email alerts
|

A Large Area Pixelated Silicon Array Detector for Independent Transit In Vivo Dosimetry

Abstract: A large area pixelated silicon array detector named “MP987” has been developed for in vivo dosimetry. The detector was developed to overcome the non-water equivalent response of EPID (Electronic Portal Imaging Device) dosimetry systems, due to the shortfalls of the extensive corrections required. The detector, readout system and software have all been custom designed to be operated independently from the linac with the array secured directly above the EPID, to be used in combination with the 6 MV imaging syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…5 However, film-based dosimetry is a passive technology that cannot provide the desired real-time feedback. For real-time large-area dosimetry, several solutions are available based solely on EPID or a combination of EPID and dedicated detectors, such as the solution proposed by Brace et al 6 These large-area pixelated detectors typically employ a 2D array of silicon detectors placed on the flat panel imager available on most clinical LINACs to monitor exit dose during patient treatments. Olaciregui-Ruiz et al 7 provide an extensive review of the requirements of EPID dosimetry.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, film-based dosimetry is a passive technology that cannot provide the desired real-time feedback. For real-time large-area dosimetry, several solutions are available based solely on EPID or a combination of EPID and dedicated detectors, such as the solution proposed by Brace et al 6 These large-area pixelated detectors typically employ a 2D array of silicon detectors placed on the flat panel imager available on most clinical LINACs to monitor exit dose during patient treatments. Olaciregui-Ruiz et al 7 provide an extensive review of the requirements of EPID dosimetry.…”
Section: Introductionmentioning
confidence: 99%
“…Some have replaced the metal/phosphor screen with a solid water layer [12][13][14] or plastic scintillator arrays [15][16][17][18]. Efforts have also been made developing math models to convert the measured a-Si EPID image to a water-equivalent image [19][20][21][22][23][24]. These models are typically semi-empirical and have limited robustness in clinical application, restricted to the range of IOP Publishing doi:10.1088/1742-6596/2799/1/012020 2 measurements taken (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…EPIDs are not specifically designed for patient dosimetry, and with better methods for managing patient position, they may be at risk of becoming obsolete. Several authors have demonstrated redesigned downstream dosimetry systems based on silicon with attempts to address such issues [ 10 , 11 ]. A multicentre study of commercial EPID dosimetry systems [ 12 ] found out-of-tolerance errors of up to 25%, which was due predominantly to patient anatomical changes and positioning errors; however, it concluded that EPID dosimetry was effective in intercepting important errors.…”
Section: Introductionmentioning
confidence: 99%